Asuhan Kebidanan Komprehensif Pada Ny. H Dengan Kekurangan Energi Kronik - Annisa Whusty Kholifia; Istiqomah Dwi Andari; Riska Arsita (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
AKI worldwide according to WHO in 2018, namely 108,300 In Indonesia, AKI cases in 2020, namely 6,856. In Central Java, MMR in 2021 is 1,011 with Tegal Regency at 29.78% and IMR 48 cases. Data at the Jatibogor Health Center for Chronic Energy Deficiency (KEK) cases amounted to 16.7% of a total of 840 pregnant women. Pregnant women with CED will certainly experience various health problems. The health of pregnant women is very important because it can affect the health of the baby they contain. KEK is a disease that has several risk factors and adverse effects on the mother and baby. The strategy for achieving government policy is through improving Indonesia's health in accordance with the Sustainable Development Goals (SDG) by forming quality human beings whose one of the achievements is meeting the food and nutrition needs of each individual. Collaborate with health workers to provide KIE regarding KEK and the factors that influence it and how to overcome them. One of them is counseling by spreading messages, instilling confidence. The purpose of this case study was to carry out midwifery care for pregnant women, birth mothers, postpartum women, and newborns in a comprehensive manner using midwifery care management according to Varney and documentation using the SOAP method. The object of this case is Mrs. H G1P0A0, 27 years old with normal pregnancy, childbirth and postpartum. This case study was carried out in October 2022 in the working area of ​​the Jatibogor Health Center. The care is described in its entirety, starting from the patient's TM III pregnancy (39 weeks to 41 weeks) and normal postpartum (9 hours postpartum to 40 days postpartum). The processed results are Comprehensive Midwifery Care for Ny. H since the age of 39 weeks, during labor until puerperium 40 days postpartum. The compilation concludes that the gestation period is normal, delivery by SC, BBL and postpartum are normal.